2021
DOI: 10.1016/j.plabm.2020.e00195
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of performance of clinical biochemistry laboratory using Sigma metrics and Quality Goal Index

Abstract: Background Unreliable and ingenuine results issued by clinical laboratories have serious consequences for the patients. Sigma metrics is a standardized tool for Quality assessment for test performance in a laboratory. Objective To evaluate the performance of routine biochemistry laboratory at MMIMSR, Mullana in terms of Sigma metrics and Quality Goal Index. Material and methods This cross sectional study evaluated performance of 14 routine ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The differences in sigma of the same analyte at different levels of QC material is ultimately due to makeable difference in CV% which is an indicator of poor precision mainly attributed to laboratory personnel and environment. Moreover, this finding is identical to other studies [10,17,18,21] . The discrepancy between the QC material levels can partly be attributed to methodology used for some analytes, which might indicate different performance between normal or abnormal concentrations of the QC materials [17] .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The differences in sigma of the same analyte at different levels of QC material is ultimately due to makeable difference in CV% which is an indicator of poor precision mainly attributed to laboratory personnel and environment. Moreover, this finding is identical to other studies [10,17,18,21] . The discrepancy between the QC material levels can partly be attributed to methodology used for some analytes, which might indicate different performance between normal or abnormal concentrations of the QC materials [17] .…”
Section: Discussionsupporting
confidence: 92%
“…The current study went ahead to determine QGI for the analytes with σ 4 for purposes of identifying the problem cause. Majority of the poor to unacceptable analyte performance was due to imprecision (random errors), with only four analytes implicated to inaccuracy (systematic errors).Similar findings are in several previous studies implying most errors encountered in clinical laboratories are human and environmental errors [10,17,18,21] . In addition, σ values are influenced mainly by two inputs, bias and imprecision, which can be influenced by several factors within a clinical laboratory.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…(3) monitor the calibration cycle of the detection system to reduce system errors; and (4) improve the maintenance of the instrument, replace old parts in a timely fashion, and improve the stability of the detection system. The research carried out by Goel et al 36 showed that QGI was very helpful for guiding a laboratory in determining the reasons for the poor performance of routine chemistry analyses and for guiding the adoption of appropriate improvement measures.…”
Section: Discussionmentioning
confidence: 99%